Evaluation on the Responsiveness of Science Technology Engineering (STE) Program in Region XII, Philippines - Cherwin Macaranas; Ava Clare Marie O. Robles (East Asian Journal of Multidisciplinary Research, 2023)
In Philippine Basic Education, offering of special curricula is a robust practice. Needless to say, limited evaluation as to the responsiveness of curriculum prevails up to date. This study was conducted to evaluate the responsiveness of Science Technology Engineering as a special curricular program in schools. This inquiry was conducted among 32 administrators, 129 teachers and 241students among STE implementing schools. It determined the level of responsiveness of STE in meeting the needs of the learners, the extent of learning opportunities gained by students and the extent of barriers faced by teachers. Findings revealed an overall “high level” of responsiveness of STE program. Students rated the program with “high extent of learning opportunities” from the implementation. While teachers claimed of being “moderately challenged” in implementing the program. These results imply that schools have been consistently meeting the requirements and standards of the STE curriculum in the country.